Obama, the media, and framing the U.S. exit from Iraq and Afghanistan - King, Erika G. (Routledge, 2016)
Situating Obama's end-of-war discourse in the historical context of the 2001 terrorist attacks, Obama, the Media, and Framing the U.S. Exit from Iraq and Afghanistan begins with a detailed comparison with the Bush war-on-terror security narrative before examining elements of continuity and change in post-9/11 elite rhetoric. Erika King deftly employs two case studies of presidential and media framing - the weeks surrounding the formal announcements of Obama's December 2009 'surge-then-exit' strategy from Afghanistan and the end of combat operations in Iraq in August 2010 - to explore the role of mass media in presenting presidential narratives of war and finds evidence of an interpretive disconnect between the media and a president seeking to present a more nuanced approach to keeping America safe. Eloquently scrutinizing Obama's discourse on the U.S. exit from two post-9/11 wars and contrasting the presidential endgame frame with the U.S. mainstream media's narratives of the wars' meaning, accomplishments, and denouement provides a unique combination of qualitative content analysis and topical case studies and makes this volume an ideal resource for scholars and researchers grappling with the complicated and ever-evolving nexus of war, the president, and the media.